Rapid achievement of low disease activity during the use of a type I interferon inhibitor in a patient with torpid systemic lupus erythematosus (case report) - A. A. Baranov; E. A. Aseeva; S. K. Soloviev; N. Yu. Nikishina; E. A. Malygina; T. O. Abissova; Z. Yu. Pimenova; T. M. Reshetnyak; S. A. Makarov; N. A. Lapkina; A. M. Lila (Современная ревматология, 2024)
This article describes the experience of using the type I interferon inhibitor anifrolumab (AFM) in a patient with a torpid course of systemic lupus erythematosus. The reason for prescribing AFM was the need for a quick achievement of low disease activity due to a planned hip replacement. Dynamic observational data over a six-month period confirmed that AFM enables a rapid achievement of low disease activity without increasing the dose of glucocorticoids, significantly improve the patient's quality of life and even prepare them for major surgery without exacerbating the underlying process.